Analysis The Strategy In Improving Students Reading Comprehension of “ Content Area Reading and Learning” English Book - Evawati Nainggola; Rebekka Basa Natalia Samosir; Ester Riska Sianturi; Erikson Saragih (Institut Agama Islam Negeri Palopo, 2021)
This research is intended to know whether the teaching and learning process of reading comprehension using the Content Area Reading and Learning English Book helps to develop students' understanding and people who want to master English language skills, one of which is reading, in overcoming reading comprehension problems using reading books will increase structure or strategy. This research uses qualitative methods. The writing of this scientific paper aims to find out what strategies are used in developing students' skills or abilities, as well as those who want to master the English reading skills which are the basis of English before reaching writing and speaking, and according to the application in the Content Area Reading and Learning English Book, and the results of the research strategy used in learning to read are small group teams towards clearly articulated goals.